Pregnancy outcome in women with congenital heart disease in a tertiary care centre - Lipika Adhikari; Sandip Sarkar; Amitava Das; Priyanka Sannigrahi; Prateek Chawdhary (Barpeta Obstetrics and Gynaecological Society, 2018)
Objective: To find out prevalence of congenital heart disease in pregnant women and its cardiac, obstetric and neonatal outcome. Methodology: A prospective study was conducted on 74 mothers who had congenital heart disease and admitted in Obstetrics and Gynaecology department during a period of December 2013 to December 2017. Baseline data were collected before pregnancy or at the first antenatal visit. These included clinical presentation, ECG, chest X ray, echodoppler study and subsequently maternal cardiac event, obstetric outcome, neonatal event and risk stratification of bad obstetric outcome. Result: During the study period 74 women having congenital heart disease (CHD) were seen. The prevalence of congenital heart disease was 0.14%. Most of the patients had atrial septal defect (ASD) (35%). Normal delivery was in 18 numbers of patients and most of these were ASD and pulmonary stenosis. Large number of patients had developed complication of sustained arrhythmia (41%). Pulmonary oedema was documented in 8 patients. Seven patients expired during labour and puerperium. Regarding fetal outcome 58% pregnancy had intrauterine growth restriction, 67% had preterm birth and 8% had neonatal death. Conclusion: Maternal and neonatal complication rates are considerably high in pregnant women with congenital heart disease.